PENINGKATAN KETERAMPILAN MENULIS DIALOG SEDERHANA MENGGUNAKAN METODE TERBIMBING DI KELAS V SEKOLAH DASAR - Hartanto, Pandu; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe the use of guided methods assisted audio visual media to improve the writing skills of simple dialogue. The research procedure consists of planning, implementation, observation, and reflection. Research subjects were teachers and students of grade V. Techniques of collecting data in the form of observation, documentation and questionnaire. Data analysis techniques by qualitative descriptive analysis used to analyze the data in the form of descriptions accompanied by simple calculations, and the presentation of data averages and percentages are then changed in the form of tables and graphs. The results showed in the first meeting of cycle I, the average score of 49.3 with a classical completeness of 4.16%. During second meeting of cycle I, experienced an increase of 20.49 to 69.79 with a classical completeness of 45.83%. In the first meeting of cycle II increased by 12.67 to 82.46 with a classic of 73.07%, then in the second meeting of cycle II increased again by 5.38 to 87.84 with a classical completeness 100%. Based on the exposure, it can answer the common problem that using audio visual media with a guided method can improve the writing skills of simple dialogue of grade V student on Public Elementary School 02 Balai Karangan.Â Keywords: Audio Visual Media, Guided Methods, Writing skills, Simple Dialogue.